2010
DOI: 10.4102/jamba.v3i1.33
|View full text |Cite
|
Sign up to set email alerts
|

Assessing urban fire risk in the central business district of Dar es Salaam, Tanzania

Abstract: Buildings as infrastructure along with people’s lives need protection against fire outbreaks. Knowledge on the use of installed facilities is essential in tackling There emergencies, otherwise their installation becomes meaningless. Lack of such knowledge could hamper escape from There hazards and thwart attempts to contain there outbreaks at their preliminary stage. THis study, carried out in the Central Business District of Dar es Salaam City, assessed urban there risk with respect to public awareness on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 1 publication
3
14
0
Order By: Relevance
“…Rahim et al [14] revealed that involvement in related fire safety programmes was the most effective method of educating building occupants on fire safety. Kachenje et al [6] disclosed that only 29% respondents of the surveyed buildings had received training within the past five years. Makushita [8] established that trainings for steps to be taken in case of fire, first aid, search and rescue trainings have never been organized for all residents living in studied high-rise buildings.…”
Section: Training and Knowledge Of Fire Safety Measuresmentioning
confidence: 99%
See 4 more Smart Citations
“…Rahim et al [14] revealed that involvement in related fire safety programmes was the most effective method of educating building occupants on fire safety. Kachenje et al [6] disclosed that only 29% respondents of the surveyed buildings had received training within the past five years. Makushita [8] established that trainings for steps to be taken in case of fire, first aid, search and rescue trainings have never been organized for all residents living in studied high-rise buildings.…”
Section: Training and Knowledge Of Fire Safety Measuresmentioning
confidence: 99%
“…Rahim et al [14] pointed out that respondents' levels of awareness were rather low as most of assessed parameters indicated moderately effective. Kachenje et al [6] disclosed that 60% of building users do not know how to operate the facilities and 41% are not aware of available escape means in case of fire outbreak. Hayward [12] disclosed that, in one study, respondents were presented with six different signs and everyone understood the "NO SMOKING"…”
Section: Training and Knowledge Of Fire Safety Measuresmentioning
confidence: 99%
See 3 more Smart Citations